The impact of oral rehabilitation coupled with healthy dietary advice on the nutritional status of adults: A systematic review and meta-analysis. Issue 13 (19th July 2020) - McGowan, Laura; McCrum, Leigh-Ann; Watson, Sinead; Cardwell, Christopher; McGuinness, Bernadette; Rutherford, Helen; Paice, Victoria; Moore, Ciaran; Brocklehurst, Paul R.; Woodside, Jayne V.; McKenna, Gerald
Abstract: As natural teeth are lost, many older adults choose softer foods lacking in essential micronutrients and fiber, yet replacing missing teeth alone does not positively influence diet. Dietary intervention in combination with treatment to replace missing teeth is increasing, though understanding of effective intervention components is limited. This systematic review synthesized literature relating to oral rehabilitation coupled with dietary intervention in adults. The primary outcome was dietary intake; secondary outcomes pertained to oral health and dietary intervention characteristics including: theoretical basis and behavior change techniques (BCTs). MEDLINE, Web of Science, PubMed and CENTRAL were searched. Nine studies were included. Study designs were heterogeneous involving 526 participants. Narrative synthesis identified improvements in at least one aspect of participants' oral health (i.e. biting/chewing) alongside at least one positive diet/nutrition outcome post-intervention for all studies. F/V results were pooled for three studies using meta-analysis techniques resulting in a standardized mean difference (SMD) of 0.29 [CI −0.54, 1.12], p = 0.49, but with marked heterogeneity ( p = 0.0007). Few interventions were theory-based and intervention components were poorly described. Overall, narrative synthesis indicated support for dietary intervention coupled with oral rehabilitation on diet. Meta-analysis was only possible with three studies highlighting limitations. Large-scale, appropriately described trial methodologies are needed. Trial registry: This review was prospectively registered with PROSPERO on the 11 July 2017 [CRD42017071075].